Group Counseling: Reducing Cheating Behavior with a Rational Emotive Behavior Therapy Approach - Harahap, Marianna; Netrawati, Netrawati; Nirwana, Herman; Hariko, Rezki (International Journal of Applied Counseling and Social Sciences, 2023)
Cheating behavior is an activitythat appear to accompany teaching and learning process activities that can erode positive personality in students because they use dishonest methods in achieving academic grades. This study aims to test the effectiveness of group counseling with a rational emotive behavior therapy approach to reduce students' cheating behavior. This type of research is a quantitative research with the type of experimental research. The type of experimental design in this study was Quasi Experiment with The Non-Equivalent Control Group Design. The population in this study were students of SMAN 6 Padang and students of SMAN 3 Padang as many as 543 students. The sample in this study was 400 students, and 16 students were taken which were divided into 8 students for the experimental group and 8 students for the control group. Sampling used purposive sampling. This study used a data collection tool in the form of a cheating behavior questionnaire. The results of this study indicate that group counseling services using a rational emotive behavior therapy approach are effective in reducing students' cheating behavior. So that this research can be used as input material as a basis for counseling teachers/counselors in providing group counseling services using a rational emotive behavior therapy approach in an effort to overcome and prevent students' cheating behavior.